Outcomes and safety of mechanical thrombectomy, alteplase, and conventional medical care in the treatment of acute M2 segment middle cerebral artery occlusion: a comparative study - Eman M. Khedr; Ahmed Elbassiouny; Mahmoud Nageeb; Ahmed Aly; Khalid O. Mohamed; Nourelhoda A. Haridy (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Data on mechanical thrombectomy (MT) to treat M2 occlusions of the middle cerebral artery (MCA) are sparse. We report the outcome and safety of MT versus intravenous recombinant tissue plasminogen activator (IV rTPA) versus conventional medical treatment (CMT) of acute ischemic stroke (AIS) due to occlusion of the M2 segment of the MCA. This prospective longitudinal intervention study compared the outcomes and safety of MT, rTPA, and CMT in M2 occlusion AIS patients. National Institutes of Health Stroke Scale (NIHSS), modified Rankin scale (mRS), and recanalization rate assessed outcomes. Results 74 AIS patients were recruited (23 MT, 23 rTPA, 28CMT). MT group had significantly higher admission NIHSS (p = 0.018) and mRS (p = 0.023) than rTPA. At 24 h, NIHSS improved more with MT and rTPA than CMT (p < 0.0001). At 3 months, mRS were better with MT and rTPA versus CMT (p < 0.0001). Successful recanalization occurred in 73.9% of the MT group. 69% of the MT group required stent retrieval plus aspiration thrombectomy, and 60.9% required ≥ 3 trials, but outcomes did not differ by technique or number of trials. A good outcome (mRS 0–2) at 3 months was achieved in 69.6% MT versus 65.2% rTPA versus 7.1% CMT (p < 0.0001). Symptomatic intracranial hemorrhage (sICH) rates were slightly, but insignificantly, higher with CMT. Mortality did not significantly differ between groups. Conclusions For M2 occlusions, MT and rTPA achieved better early and 3-month outcomes than CMT; however, MT was not superior to rTPA. MT of M2 is feasible and effective, with a lower hemorrhage rate than rTPA and CMT. Trial registration: This study was prospectively registered in the clinical trial with ClinicalTrials.gov ID (NCT05091320). The link: https://clinicaltrials.gov/study/NCT05091320